Interventions in foster and kinship care: A systematic review. (July 2013) - Kinsey, Debbie; Schlösser, Annette
Foster care is a complex setting in which to provide therapeutic interventions due to the high rates of difficulty, poor outcomes and high numbers of professionals and carers involved. This systematic review aims to examine interventions that have been empirically assessed in foster care. Thirty papers describing 20 interventions were included. It was found that there was good support for wraparound services and relational interventions, but little support for widely used carer training programmes. A need was identified to further research and implement wraparound services within the UK, and to empirically test interventions which may be efficacious with a foster care population.